Long‐Term Survival and Risk of Institutionalization in Onco‐Geriatric Surgical Patients: Long‐Term Results of the PREOP Study. Issue 6 (10th March 2020) - Huisman, Monique G.; Ghignone, Federico; Ugolini, Giampaolo; Sidorenkov, Grigory; Montroni, Isacco; Vigano, Antonio; de Liguori Carino, Nicola; Farinella, Eriberto; Cirocchi, Roberto; Audisio, Riccardo A.; de Bock, Geertruida H.; van Leeuwen, Barbara L.
Abstract : OBJECTIVES: To evaluate long‐term survival and institutionalization in onco‐geriatric surgical patients, and to analyze the association between these outcomes and a preoperative risk score. DESIGN: Prospective cohort study with long‐term follow‐up. SETTING: International and multicenter locations. PARTICIPANTS: Patients aged 70 years or older undergoing elective surgery for a malignant solid tumor at five centers (n = 229). MEASUREMENTS: We assessed long‐term survival and institutionalization using the Preoperative Risk Estimation for Onco‐geriatric Patients (PREOP) score, developed to predict the 30‐day risk of major complications. The PREOP score collected data about sex, type of surgery, and the American Society for Anesthesiologists classification, as well as the Timed Up & Go test and the Nutritional Risk Screening results. An overall score higher than 8 was considered abnormal. RESULTS: We included 149 women and 80 men (median age = 76 y; interquartile range = 8). Survival at 1, 2, and 5 years postoperatively was 84%, 77%, and 56%, respectively. Moreover, survival at 1 year was worse for patients with a PREOP risk score higher than 8 (70%) compared with 8 or lower (91%). Of those alive at 1 year, 43 (26%) were institutionalized, and by 2 years, almost half of the entire cohort (46%) were institutionalized or had died. A PREOP risk score higher than 8 was associated with increased mortality (hazard ratio = 2.6; 95% confidence interval [CI] = 1.7‐4.0), irrespective of stage and age, but not with being institutionalized (odds ratios = 1 y, 1.6 [95% CI = .7‐3.8]; 2 y, 2.2 [95% CI = .9‐5.5]). CONCLUSION: A high PREOP score is associated with mortality but not with remaining independent. Despite acceptable survival rates, physical function may deteriorate after surgery. It is imperative to discuss treatment goals and expectations preoperatively to determine if they are feasible. Using the PREOP risk score can provide an objective measure on which to base decisions. J Am Geriatr Soc 68:1235–1241, 2020.